Sclerosing melanocytic lesions (sclerosing melanomas with nevoid features and sclerosing nevi with pseudomelanomatous features) - an analysis of 90 lesions - Grčar-Kuzmanov, Biljana (Radiology and oncology (Ljubljana), 2018)
Background. Sclerosing melanocytic lesions, which are characterized by either focal or diffuse sclerosis in the dermal component and atypical proliferation of predominantly nevoid melanocytes, remain poorly defined. Our aim was to analyze systematically their morphologic spectrum, especially the distinction between sclerosing melanocytic nevus and sclerosing melanoma, which has not been well documented. Patients and methods. We collected 90 sclerosing melanocytic lesions, occurring in 82 patients (49 male, 33 female; age range from 21 to 89 years). A four probe fluorescent in situ hybridization (FISH) assay was performed in 41 lesions to substantiate the diagnosis of sclerosing melanomas. Results. A prominent full-thickness pagetoid spread of melanocytes was identified in 44 (48%) lesions, and a melanoma in situ adjacent to the sclerosis in 55 (61%) lesions. In the intrasclerotic component, maturation was absent in 40 (44%) and mitotic figures were identified in 18 (20%) lesions. Of the 90 lesions, 26 (29%) were diagnosed morphologically as nevi and 64 (71%) as melanomas (Breslow thickness from 0.4 to 1.8 mm), including 45 (50%) melanomas with an adjacent nevus. A four-probe FISH assay was positive in the sclerotic component in 14 of 25 lesions diagnosed morphologically as melanomas and none of 16 nevi. A sentinel lymph node biopsy was performed for 17 lesions and was negative in all cases. Conclusions. Sclerosing melanocytic lesions form a morphologic spectrum and include both nevi and melanomas. The pathogenesis of sclerosis remains obscure but seems to be induced by melanocytes or an unusual host response in at least a subset of lesions.
Keywords: fibrosis; fibroza; sclerosing melanoma; sclerosing nevus; sklerozirajoči melanom; sklerozirajoči nevus